Turkish And Brics Engagement In Africa - Tepeciklioglu, Elem Eyrice; Tok, Mohammed Evren; Basher, Syed (Journal of Sustainable Development Law and Policy, 2025)
This article studies the political economy of Turkey’s relations with sub-Saharan Africa (SSA) since 2002 while Turkey was under the Justice and Development Party’s (AKP) rule. It argues that Turkey has focused its engagement in Africa mostly on humanitarian assistance and the economy. Contextualizing Turkey’s relations with SSA vis-à-vis other emerging market economies, especially the BRICS (Brazil/Russia/India/China/South Africa), provides ample insights into the nature of Turkey’s engagement in SSA. While Turkey’s involvement has some similarities with that of the BRICS, there are greater fundamental and structural differences from how the BRICS established their presence in SSA. These differences mostly find resonance when juxtaposed with the activism of non-governmental actors engaged in humanitarian missions and charity work with trade-related economic investments and activism.